The Decentralization Dilemma in India - Purfield, Catriona (IMF Working Papers; Working Paper, 2004)
Already in precarious shape, the financial health of India's states took a turn for the worse in the late 1990s when state deficits and debt rose sharply. While India is among the world's most decentralized economies, greater decentralization is not the root cause of this situation. Panel estimation techniques find evidence that the trend rise in deficits reflects problems of transfer dependence and moral hazard that undermine states' incentives to control deficits.